Greckie wpływy na powstanie Ustawy XII Tablic : (na marginesie glosy Accursiusa do D. 1,2,2,4) - Wołodkiewicz, Witold (Prawo Kanoniczne, 1994)
The problem of Greek influence on the creation and the content of the Twelve Tables appeared several times in Roman lawyers’ records. Amongst few jurists, Pomponius wrote about the influence of Greek cities law on the Twelve Tables in the famous fragment on the history of Roman law from his Enchiridion (D. 1,2,2,3-4). Accursius gave an ample gloss to the fragment. He cites an anecdote on the creation of the Twelve Tables: „Greeks had delegated a wise man to visit Rome in order to estimate, after a discussion with its inhabitants, whether they are mature enough to be presented with the law that was prepared. Romans reached the decision that a fool should confront the Greek: there would be no damage to them if he lost, they thought. Obviously, both had to speak by signs. „The Greek started the duel raising one finger what meant that he believed in one God. The Roman took it as an attack on his eye and showed two fingers, which made three with his thumb, in order to be dangerous for both eyes of his adversary. However, the visitor understood the gesture as an acceptance of faith in one God with addition that He is triune. Referring to that, the Greek showed an open palm - it signified that everything is known to the Almighty. Yet, the fool thought that it is to strike his hand and raised the fist to demonstrate that he was going to defend himself. The wise man from Greece understood it as a statement that God has human fortune in His hand and reigns over all affairs of this world. „After this conversation, the Greek concluded that Roman society is developed in the degree they can be gifted with the prepared statue” . The story is one of the first notes on Greek influence on the Twelve Tables. It shows the total lack o f historic perpsective that was shared by glossators in the Middle Ages. The article contains also some references to the historiography of the Greek influence on the Twelve Tables.